Vitamin D and Calcium Levels in Children With Nephrotic Syndrome, Surveillance in a Tertiary Medical Center: Vitamin D and Calcium Levels in Children With Nephrotic Syndrome - Alizadeh, Yavar; Bazargani, Behnaz; Fahimi, Dariush; Abbasi, Arash; Askarian, Fahimeh; Taheri, Amin; Moghtaderi, Mastaneh (Journal of Pediatric Nephrology, 2023)
Background and Aim: The incidence rate of nephrotic syndrome (NS) is 2-7 children per 100,000 children. Children with NS usually have some calcium homeostasis problems leading to abnormal bone histology, hypocalcemia, reduced serum vitamin D metabolites, and impaired intestinal absorption of calcium during their disease or following treatment. Methods: This is a prospective study on patients with NS on their first visit before any initial treatment. One hundred and three children aged 2-12 years referring to our nephrology department from March 2018 to June 2019 were enrolled in this study. Serum concentrations of calcium, phosphorus, albumin, 25(OH)2 vitamin D3, and creatinine were measured in all patients. The correlation of 25(OH) vitamin D3 with the type of nephrotic syndrome, gender, and age of the patients was evaluated. Results: Sixty-two patients were male (60.2%) and 41 cases were female (39.8%). Vitamin D deficiency (<20 ng/dL) was observed in 87 out of 103 patients (96.7%). Also, 24 patients underwent kidney biopsy: ten patients were found with minimal change disease (41.7%), seven patients (29.2%) showed focal segmental glomerulosclerosis, and seven cases had diffuse mesangial proliferation. Mean serum levels of calcium, phosphorous, albumin, and cholesterol were 7.512, 4.756, 1.932, and 450.68 mg/dL, respectively, and there was no correlation between vitamin D levels and these parameters except albumin. Conclusion: Because of the high prevalence of vitamin D deficiency and its serious consequences in NS patients, it is recommended to measure the levels of this vitamin at the first visit and treat this deficiency, if necessary, along with other specific treatments.